2004
DOI: 10.1016/j.ics.2004.01.094
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytospermia

Abstract: The role of leukocytes in semen (leukocytospermia) is still controversial. Contradictory reports on leukocytospermia have been published indicating negative effects on semen parameters and even in vitro fertilization (IVF) results, while other investigators did not find any negative influences of leukocytospermia on semen parameters. A few papers indicated a positive role for seminal leukocytes by elimination of morphological abnormal spermatozoa by phagocytosis. However, from the most recent literature, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Other conditions that also increase sperm oxidative stress can be treated by surgery (varicocele)73 by the use of corticosteroids (presence of anti-sperm antibodies following chronic genital tract inflammations)151152153 and the correct and timely use of antibiotics for genital tract infections 154155156…”
Section: Preventive and Therapeutic Approaches To Improve Sperm Motilitymentioning
confidence: 99%
“…Other conditions that also increase sperm oxidative stress can be treated by surgery (varicocele)73 by the use of corticosteroids (presence of anti-sperm antibodies following chronic genital tract inflammations)151152153 and the correct and timely use of antibiotics for genital tract infections 154155156…”
Section: Preventive and Therapeutic Approaches To Improve Sperm Motilitymentioning
confidence: 99%
“…On the one hand, some authors demonstrated poor sperm morphology characteristics in the presence of several types of bacteria (Table 1). Also, the improvement in sperm parameters including sperm morphology abnormalities in men with urogenital tract infections after long-term antibiotic treatment has been observed [40]. On the other hand, sperm morphology alterations associated with elongation and reduced acrosomal inducibility have been found in men with inflammatory chronic prostatitis/chronic pelvic pain syndrome, and these changes were attributed rather to leukocytes [41].…”
Section: Coli Staphylococcus (S) Aureus Enterococcus (E) Faecalismentioning
confidence: 99%
“…Low ICSI fertilization rates have also been found in men with severely elongated sper ma tozoa compared with other sperm morphology abnormalities [64]. However, when the MAGI is treated with long-term antibiotics or the varicocele is treated with a varicocelectomy, semen characteristics, including sperm morphology, can improve and pregnancies can result [65]. In case of varicocelectomies, in which no substantial improvement in semen quality is observed, pregnancies do still occur because sperm DNA quality improves because of the reduction of ROS production following the varicocelectomy [66].…”
Section: Elongated Spermatozoamentioning
confidence: 99%
“…Although not actually a sperm morphology parameter, determination of the presence of leukocytes, especially polymorphonuclear leukocytes, is an important aspect of the sperm morphology evaluation procedure [65]. Polymorphonuclear leukocytes are the main source of ROS production in semen, leading to increased sperm DNA damage.…”
Section: Detection Of Leukocytesmentioning
confidence: 99%
See 1 more Smart Citation